Methodology of the annual livestock assessment and development model (LEAD) for China: Calculation Rules and Farm Level Environmental Performance Parameters - Hongmin, Dong; Wei, Sha (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This report is an explanation of the computational methodology of the annual Livestock Environmental Assessment and Development (LEAD) model for China. The methodology developed using these conceptual calculation rules aims to introduce a harmonized scientific and reliable approach to the assessment of the nitrogen and phosphorus flows and environmental emissions of milk production on dairy farms. It aims to increase the understanding of milk supply chains and to help improve their environmental performance. The LEAD model will allow individual processing companies and farms in the dairy sector to assess the environmental impact associated with their production system or chain and aims to give suggestions on how to change their farm management to improve their dairy production system and environmental performance. The present methodology of the LEAD model is not intended to remain static. It will be updated and improved as the sector evolves and as new methodological frameworks and data become available. Keywords: Nutrient flow; nitrogen; phosphorus; environmental emissions; manure treatment